A Facile Strategy to Achieve Synergistic Multiple Hydrogen Bonding Interactions for Constructing Robust Hydrogels with Self‐healing Capability, Shape Transformation and Actuation Function. Issue 6 (1st February 2021) - Yang, Jumin; Cristian, Valenzuela; Dong, Anjie; Zhang, Jianhua
Abstract: The double network (DN) hydrogels, especially the physically crosslinked DN hydrogels, have attracted increasing attention due to their high reconfigurability, multi‐sensitivity, and efficient energy dissipation, but their applications still suffer from the relatively low mechanical strength, complex preparation process, and insufficient functionality. In this work, a simple but efficient strategy to fabricate robust and multitasking polyvinyl alcohol (PVA)/poly( N ‐acryloyl glycinamide) (PNAGA) DN hydrogels via an ultraviolet (UV)‐initiated one‐pot in situ polymerization and a subsequent freezing‐thawing treatment is reported. The PVA/PNAGA DN hydrogels are fully physically linked DN network via multiple hydrogen bonding interactions, which contain hard PVA crystalline microdomains and soft PNAGA regions. The synergetic multiple hydrogen bonding interactions and the cooperation of hard and soft regions in PVA/PNAGA hydrogels as well as the polyhydroxy matrix can not only impart the PVA/PNAGA hydrogels with super mechanical strength, high toughness, good stretchability, and rapid shape‐recoverability, but also endow the hydrogels with tailorable self‐healability, multiple shape memory, and actuation function. Considering the easily available materials, simple preparation process, and highly multitasking properties, this novel strategy should greatly enrich the methodological toolbox for the synthesis of robust and multifunctional hydrogels for the diversity of applications. Abstract : Multifunctional hydrogels demonstrate great promise for multifarious applications. Herein, by constructing double network hydrogel based on synergetic multiple hydrogen bonding interactions, a robust and multitasking hydrogel with high mechanical properties, self‐healability, multiple shape memory, and actuation function is readily obtained, providing a cost‐effective and easy‐to‐implement strategy to fabricate multifunctional hydrogels.